A positive genotype–phenotype correlation in a large cohort of patients with Pseudohypoparathyroidism Type Ia and Pseudo‐pseudohypoparathyroidism and 33 newly identified mutations in the GNAS gene. Issue 2 (4th December 2014) - Thiele, Susanne; Werner, Ralf; Grötzinger, Joachim; Brix, Bettina; Staedt, Pia; Struve, Dagmar; Reiz, Benedikt; Farida, Jennane; Hiort, Olaf
Abstract Maternally inherited inactivating GNAS mutations are the most common cause of parathyroid hormone (PTH) resistance and Albright hereditary osteodystrophy (AHO) leading to pseudohypoparathyroidism type Ia (PHPIa) due to Gsα deficiency. Paternally inherited inactivating mutations lead to isolated AHO signs characterizing pseudo‐pseudohypoparathyroidism (PPHP). Mutations are distributed throughout the Gsα coding exons of GNAS and there is a lack of genotype–phenotype correlation. In this study, we sequenced exon 1–13 of GNAS in a large cohort of PHPIa‐ and PPHP patients and identified 58 different mutations in 88 patients and 27 relatives. Thirty‐three mutations including 15 missense mutations were newly discovered. Furthermore, we found three hot spots: a known hotspot (p.D190MfsX14), a second at codon 166 (p.R166C), and a third at the exon 5 acceptor splice site (c.435 + 1G>A), found in 15, 5, and 4 unrelated patients, respectively. Comparing the clinical features to the molecular genetic data, a significantly higher occurrence of subcutaneous calcifications in patients harboring truncating versus missense mutations was demonstrated. Thus, in the largest cohort of PHPIa patients described to date, we extend the spectrum of known GNAS mutations and hot spots and demonstrate for the first time a correlation between the genetic defects and the expression of a clinical AHO‐feature.